Money, Religion, and Symbolic Exchange in "Winter Sleep" - Diken, Bülent (Religion and society, 2017)
Winter Sleep is the latest film from Nuri Bilge Ceylan, a Turkish director and screenwriter who has received international acclaim. For the purpose of social and cultural analysis, this article critically focuses on the film's key themes and maneuvers that have diagnostic value from a social theoretical viewpoint. These themes are religion, the relationship between religion and capitalism, and symbolic exchange. Organized around these topics, the article examines the religion-capitalism-symbolic exchange nexus by analyzing the motifs of formation, intervention, and intelligibility as these themes arise. This site of intersection is the conceptual pivot around which the article configures itself. It explores Winter Sleep based on what the film shows and says on screen, how its thought processes emerge, and at what points this thought supports or conflicts with dominant societal opinions.